Activity in child and youth care: lessons from the classroom and the field - McGrath, Jenny; Pope, Christine; Stiller, Rebecca (My University, 2023)
Organized as a text for college level Child and Youth Care students, but it also is a resource for practitioners who need a practical guide to build more effective activity-based approaches. Creating recreational experiences that are useful, fun and impactful is a very large part of working in the life space. Practitioners must be fully prepared to use activity work to support the young people and families that they serve, and this book is designed to train newer CYC staff in the complexity of doing those activities.
Keywords: creative activities; children; youth; social work